Pengaruh Beban Kerja Dan Motivasi Terhadap Kepuasan Kerja Pegawai Pada Dinas Koperasi Perindustrian Dan Perdagangan Kota Bima - Nurfitriah Ningsih; Muhammad Yusuf; Khairul Amar (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to determine the effect of workload and motivation on employee job satisfaction at the Bima City Industry and Trade Cooperative Service. The sample in this research was 45 ASN employees with the sampling technique used, namely purposive sampling. Data collection techniques use observation, questionnaires and literature study, data analysis techniques use multiple linear regression. The results of the research show that partially and simultaneously workload and motivation affect employee job satisfaction at the Bima City Industry and Trade Cooperative Service.